Practice-Based Research in Digital Arts: A Case Study of Wat Phumin, Nan Province, Thailand - Tawipas Pichaichanarong (Graduate School of Institut Seni Indonesia Yogyakarta, 2019)
ABSTRACTThai mural paintings have played a significant role in Thai society since The Sukhothai Kingdom period (1238-1438 AD) until the present. Wattana Boonjub (2009) points out that Mural painting was used for teaching the Thai people in the past. Throughout history, temples have become a crucial part of Thai' lives; for example, Wat Phumin in Nan Province. Wat Phumin has exceptional architecture, beautiful visual presentations of Buddhist storytelling on the walls which depict scenes from the Buddhist Jataka tales, and scenes of everyday life in Nan. These unique characteristics have attracted many visitors to this temple over the years. Also, when those interested visit Wat Phumin, they experience this temple as a Museum. Loïc Tallon et al. (2008) suggests that the museum experience provides an appropriate situation for learning history in an unconventional setting. As a result, previous research titled “Visual Research Practices on Thai Lanna Mural Painting: A Case Study of Wat Phumin, Nan Province” was presented at The 4th International Conference for Asia Pacific Arts Studies (ICAPAS 2016). The results indicated that the information concerning the Lanna mural paintings inside the temples was overwhelming. However, no directions are facilitating Thai and foreign visitors in viewing and understanding at the first episode of storytelling on Lanna mural paintings inside Wat Phumin. Therefore, this research is the result of finding a solution to facilitating visitors in viewing Buddhist Jataka tales through digital arts and digital technology (such as responsive web design, QR codes, etc.) with practice-based design research. ABSTRAK Lukisan mural Thailand telah memainkan peran penting dalam masyarakat Thailand sejak periode Kerajaan Sukhothai (1238-1438 M) hingga saat ini. Wattana Boonjub (2009) menunjukkan bahwa lukisan Mural digunakan untuk mengajar orang-orang Thailand di masa lalu. Sepanjang sejarah, kuil telah menjadi bagian penting dari kehidupan Thailand; misalnya, Wat Phumin di Provinsi Nan. Wat Phumin memiliki arsitektur yang luar biasa, presentasi visual yang indah dari cerita Buddha di dinding yang menggambarkan adegan dari kisah Buddha Jataka, dan adegan kehidupan sehari-hari di Nan. Karakteristik unik ini telah menarik banyak pengunjung ke kuil ini selama bertahun-tahun. Juga, ketika mereka yang tertarik mengunjungi Wat Phumin, mereka merasakan candi ini sebagai Museum. Loïc Tallon et al. (2008) menunjukkan bahwa pengalaman museum memberikan situasi yang tepat untuk belajar sejarah dalam lingkungan yang tidak konvensional. Sebagai hasilnya, penelitian sebelumnya yang berjudul “Praktik Penelitian Visual pada Lukisan Mural Lanna Thailand: Studi Kasus Wat Phumin, Provinsi Nan” dipresentasikan pada Konferensi Internasional ke-4 untuk Studi Seni Asia Pasifik (ICAPAS 2016). Hasilnya menunjukkan bahwa informasi mengenai lukisan mural Lanna di dalam kuil sangat banyak. Namun, tidak ada arahan yang memfasilitasi pengunjung Thailand dan wisatawan asing dalam melihat dan memahami episode pertama pada cerita tentang lukisan mural Lanna di dalam Wat Phumin. Oleh karena itu, penelitian ini adalah hasil dari menemukan solusi untuk memfasilitasi pengunjung dalam melihat cerita Buddha Jataka melalui seni digital dan teknologi digital (seperti desain web responsif, kode QR, dll.) dengan penelitian desain berbasis praktik.